Juridical Analysis of the Director's Responsibility for the Company's Debt which is not Sufficiently Paid Company Assets in Liquidation (Study at PT. Duta Beton Sejati in Liquidation) - Lumbantobing, Adianto; Ginting, Budiman; Sunarmi; Sukaraja, Detania (International Journal of Law Analytics, 2023)
The dissolution of a limited liability company conditions for the dissolution of a limited liability company, The problem in this research is what the responsibilities of a limited company that is in liquidation are; what are the roles and responsibilities of the liquidator in handling PT. Sejati Beton Ambassador in liquidation; and Whether the director is personally liable if the company's assets are insufficient to pay the PT's debts. The results of the research concluded that the responsibility of a liquidated limited liability company is to carry out all liquidation implementation procedures until the liquidator's accountability report is completed; PT liquidator. DBS plays a role in liquidation by applicable laws and regulations, namely based on the PT UUPT.must be followed by liquidation, which is an action related to the settlement or disposition of all the company's assets as a result of the legal.